2010
DOI: 10.1177/1062860610366031
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mortality of Patients Admitted to Internal Medicine Wards Over the Weekend

Abstract: The management of patients admitted during weekends may be compromised because the level of staffing in the hospital is often lower then. This study was conducted to assess what independent influence, if any, weekend admission might have on inhospital mortality. The authors analyzed the clinical data of 429,880 adults >14 years of age who were admitted to internal medicine wards in Spain after having presented to the hospitals' emergency departments. Overall mortality and early mortality (occurring in the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 28 publications
3
38
2
1
Order By: Relevance
“…Again, IHM rate was higher when admission occurred in post-office hours [8] and during the holidays [19] . As for WE versus WD, although a high mortality in subjects admitted during the WE has been reported by several authors, with an estimated increase of risk between 10% and 32% [14,15,[20][21][22] , in our study there was a trend in which more patients admitted during the WE died than those admitted on WD, but this was not confirmed by multivariate analysis. The results reported in the literature are not always consistent when considering the levels of hospital: the prognostic value of WE admission was identified more frequently in major teaching hospitals compared with nonteaching hospitals [23] , but no correlation between WE admission and IHM was found in patients admitted to tertiary care hospitals [24] .…”
Section: Discussioncontrasting
confidence: 87%
“…Again, IHM rate was higher when admission occurred in post-office hours [8] and during the holidays [19] . As for WE versus WD, although a high mortality in subjects admitted during the WE has been reported by several authors, with an estimated increase of risk between 10% and 32% [14,15,[20][21][22] , in our study there was a trend in which more patients admitted during the WE died than those admitted on WD, but this was not confirmed by multivariate analysis. The results reported in the literature are not always consistent when considering the levels of hospital: the prognostic value of WE admission was identified more frequently in major teaching hospitals compared with nonteaching hospitals [23] , but no correlation between WE admission and IHM was found in patients admitted to tertiary care hospitals [24] .…”
Section: Discussioncontrasting
confidence: 87%
“…8 Hospital admission during WE is associated with an increased mortality in some but not all acute medical conditions. 6,7,9 For example, acute conditions requiring urgent diagnosis and treatment (acute myocardial infarction [AMI], stroke, pulmonary embolism, rupture of abdominal aortic aneurysm, and intensive care unit [ICU] admission), seem to be associated with increased in-hospital or shortterm mortality during the WE compared with a WD. 4,5,[10][11][12] Also, medical patients admitted or discharged from the ICU early in the WE seem to have an increased mortality risk and readmission risk to the ICU.…”
mentioning
confidence: 99%
“…2,3 Several studies have shown that in patients hospitalized due to an acute cardiovascular event, a significantly higher mortality rate is present in the case of admission on weekends (WE), compared with that during weekdays (WD). [4][5][6][7] Other studies observed that although all-cause mortality was similar in patients admitted during WD or WE, admissions on WE were followed by a higher mortality within the first 48 hours. 8 Hospital admission during WE is associated with an increased mortality in some but not all acute medical conditions.…”
mentioning
confidence: 99%
“…The acute exacerbation phase entails a substantial rate of hospital mortality [6]. The recognition of risk factors for mortality among patients hospitalised for COPD can be of crucial importance for curtailing cost and reducing mortality.Several studies [7][8][9][10][11][12] concluded that weekend hospitalisation is associated with worse health outcomes. These studies are supported by the work of others [13,14], which find a positive correlation across hospitals between annual average staff-to-patients ratios and quality of care.…”
mentioning
confidence: 99%